Algorithm for Automated Design of Homogeneous Slopes in Open Pit Mines Using Limit Equilibrium Method - Mukhopadhyay, Manas; Sen, Phalguni (Journal of Mines, Metals and Fuels, 2022)
In recent years, accidents due to slope failures in openpit/ surface mines have shown an upward trend. The major factor causing such failures is the lack of scientific design of the pit and the dump slopes in mines and therefore, an optimum design of slope angle vis-à-vis slope height is of paramount importance. The slope design process is an iterative one involving large amount of computation and voluminous data, making the process a tedious and time consuming one. However, application of computer can effectively minimize these difficulties provided that a suitable computer package is available for the purpose. A good number of software are available nowadays for slope stability analysis and/or design. However, most of these software are not suitable for automated design of new slopes. In this paper, a simplified algorithm for automated design of homogeneous slopes in open pit/surface mines using limit equilibrium method (LEM) has been proposed.